The Effect of Student Learning Outcomes Using A Tutorial Model With A Group Investigation (GI) Type Cooperative Model On The Ecosystem Concept In State High School - Ina Saparlina; Iman Nurjaman (Elementaria: Journal of Educational Research, 2023)
Success in the learning system is determined by several factors including teachers, students, learning models, media, and learning facilities. One of the learning models that is considered appropriate and can create new learning conditions is the tutorial model and the cooperative group investigation (GI) model. In general, this study aims to determine the influence of the two models above on student learning outcomes on the concept of ecosystem. Respondents in this study were students of grades X 5 and 6, which were determined randomly. The type of research used is with a quantitative approach, the method used is an experimental approach. The instrument used as a data collection tool in the form of learning outcomes tests as many as 25 questions out of 30 questions after being tested for validity through validity, reliability, difficulty index, and differentiating power. The test was conducted twice with pre-test and post-test in experimental class 1 and experimental class 2. Based on the results of the study showed that; 1) there is an influence of the tutorial learning model on the ecosystem concept of student learning outcomes, 2) there is an influence of the group investigation (GI) cooperative learning model on the ecosystem concept of student learning outcomes, 3) there are differences in learning activities through the tutorial model and cooperative group investigation (GI). Overall, the tutorial learning model is better and more effective for overcoming student learning activity problems on the ecosystem concept than the group investigation (GI) cooperative learning model